Nervous System Injury and Neuroimaging of Zika Virus Infection - Wu, Shanshan; Zeng, Yu; Lerner, Alexander; Gao, Bo; Law, Meng (Frontiers in Neurology, 2018)
Abstract In 2016, World Health Organization announced Zika virus infection and its neurological sequalae are a public health emergency of global scope. Preliminary studies have confirmed a relationship between Zika virus infection and certain neurological disorders, including microcephaly and Guillain-Barre syndrome. The neuroimaging features of microcephaly secondary to Zika virus infection include calcifications at the junction of gray–white matter and subcortical white matter with associated cortical abnormalities, diminution of white matter, large ventricles with or without hydrocephalus, cortical malformations, hypoplasia of cerebellum and brainstem, and enlargement of cerebellomedullary cistern. Contrast enhancement of the cauda equine nerve roots is the typical neuroimaging finding of Guillain-Barre syndrome associated with Zika virus. This review describes the nervous system disorders and associated imaging findings seen in Zika virus infection, with the aim to improve the understanding of this disease. Imaging plays a key role on accurate diagnosis and prognostic evaluation of this disease.